Displacement of submacular hemorrhage associated with age-related macular degeneration using vitrectomy and submacular tPA injection followed by intravitreal ranibizumab - Sukhpal Singh Sandhu (Dove Medical Press, 2010)
Sukhpal Singh Sandhu1,2, Sridhar Manvikar1, David Henry William Steel11Sunderland Eye Infirmary, Sunderland, United Kingdom; 2Centre for Eye Research Australia, Melbourne, AustraliaBackground/aims: To evaluate retrospectively the clinical outcomes of patients presenting with submacular hemorrhage (SMH) secondary to neovascular age-related macular degeneration (nAMD), treated by vitrectomy, submacular tissue plasminogen activator (tPA) injection and pneumatic displacement of SMH with air followed by postoperative intravitreal ranibizumab (RZB).Methods: Patients with SMH and nAMD had 25-guage vitrectomy and subretinal tPA (12.5 micrograms/0.1 mL) with fluid/air exchange. Intravitreal RZB was administered postoperatively to patients eligible for National Health Service (NHS) funded treatment.Results: Of the total of 16 patients, 11 (68.7%) had complete displacement of SMH. The remaining five had residual SMH, mainly subretinal pigment epithelium in location. Three of the four patients who previously had a failed expansile gas pneumatic displacement were successfully displaced with vitrectomy surgery. At presentation 5/16 (31.3%) patients were eligible for NHS funded intravitreal RZB. This increased to 12 patients after the vitrectomy procedure (75.0%). At 6 months postoperatively all improved by $1 line. Ten of the 16 patients (63%) improved by ≥2 lines, with 10 of the 12 patients (83%) treated with RZB improving by ≥2 lines.Conclusion: Vitrectomy/subretinal tPA/air to displace SMH followed by intravitreal RZB injection can stabilize/improve vision in patients with nAMD. This technique displaces hemorrhage not displaced by attempted expansile gas techniques.Keywords: submacular hemorrhage, neovascular age-related macular degeneration, vitrectomy, tissue plasminogen activator, ranibizumab